Dari Tradisi Pesantren ke Pendidikan Sekolah: Transformasi Nilai Trilogi dan Panca Kesadaran Santri dalam Projek Penguatan Profil Pelajar Pancasila - Muhammad Zaki Maulana; Misbahul Arifin; Hefniy Hefniy (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2025)
Moral decadence among adolescents, the weak internalization of Pancasila values, and students’ low awareness in embodying Islamic character values constitute serious challenges for multiple stakeholders. This community engagement initiative aims to analyze and strengthen the role of teachers as facilitators in implementing the Pancasila Student Profile Strengthening Project (P5), particularly in supporting the construction and internalization of the Trilogy and the Five Awareness Principles of Santri at SMA Nurul Jadid Paiton, Probolinggo. The activities were designed as a form of service, training, and mentoring for teachers in managing P5 activities integrated with Islamic character education values. The study employed a community-based participatory research (CBPR) approach. Data were collected through in-depth interviews, observations, and documentation involving teachers, students, and the school principal as primary participants. The findings suggest that teachers play a pivotal role in designing, facilitating, and evaluating P5 projects that are grounded in local values and enriched with spiritual dimensions. Teachers act as agents of change by guiding students to understand and internalize the values of the Trilogy and the Five Awareness Principles of Santri through collaborative, contextual, and meaningful project-based learning. The implication is that enhancing teachers’ capacity through continuous training and institutional support becomes a key determinant of the successful implementation of P5 in strengthening character education based on Islamic values. Keywords: Teacher Roles; Character Education; P5 Project; Trilogy and Five Awareness Principles of Santri Dekadensi moral di kalangan remaja, lemahnya internalisasi nilai Pancasila, dan rendahnya kesadaran siswa dalam menghayati nilai karakter Islami menjadi tantangan serius bagi berbagai pihak. Tujuan pengabdian ini adalah menganalisis dan menguatkan peran guru sebagai fasilitator dalam implementasi Projek Penguatan Profil Pelajar Pancasila (P5), khususnya dalam mendukung konstruksi dan internalisasi karakter Trilogi dan Panca Kesadaran Santri di SMA Nurul Jadid Paiton Probolinggo. Kegiatan dirancang sebagai bentuk pelayanan, pelatihan, dan pendampingan terhadap guru dalam mengelola kegiatan P5 yang terintegrasi dengan nilai-nilai pendidikan karakter Islam. Metode yang digunakan adalah community-based participatory research (CBPR). Data dikumpulkan melalui wawan-cara mendalam, observasi, dan dokumentasi yang melibatkan guru, siswa, serta kepala se-kolah sebagai partisipan utama. Hasil kegiatan menunjukkan bahwa guru berperan strategis dalam merancang, memfasilitasi, dan mengevaluasi projek P5 yang berbasis nilai lokal dan bernuansa spiritual. Guru berfungsi sebagai agen perubahan dalam membimbing siswa me-mahami serta menginternalisasi nilai Trilogi dan Panca Kesadaran Santri melalui pembela-jaran berbasis projek yang kolaboratif, kontekstual, dan bermakna. Implikasinya, peningkatan kapasitas guru melalui pelatihan berkelanjutan dan dukungan kelembagaan menjadi kunci keberhasilan implementasi P5 dalam penguatan pendidikan karakter berbasis nilai Islam. Kata kunci: Peran Guru, Pendidikan Karakter, Projek P5, Trilogi dan Panca Kesadaran Santri